Peer effects among friends on students' cognitive abilities: An analysis based on emotional distance. - Wenyi Zhou; Junming Xie; Jinsong Kuang; Yongqing Feng; Dag Øivind Madsen (PLoS ONE)
In contemporary society, students' cognitive abilities are crucial for the accumulation of human capital. Consequently, significant concern has been expressed regarding the impact of peer effects among friends on students' cognitive abilities. Based on the "China Education Tracking Survey" data, we discuss peer effects among friends on students' cognitive abilities from the perspective of Emotional Distance Analysis. Our study shows that: (1) Students' average scores could be actively affected by the increase in the number of friends with good grades. (2) Peer effects among friends are in accord with different students. Such effects are more easily exerted among female students and those with better average grades or local household registration. (3) The mechanism study found that the conduction effect of peer effects among friends mainly relies on two paths. One is manifested as the "compliance effect". In other words, to align with their friends, students increase their study time, raise their educational aspirations, and minimize instances of skipping classes and absenteeism. The other channel is the "anchoring effect," which involves raising parents' reference standards, leading them to devote more time and energy to their children's learning. Therefore, the rational use of social interaction with friends is a vital approach to enhancing students' cognitive abilities.